EFECTELE TEMPERATURII RIDICATE LA DIFERITE ETAPE ONTOGENETICE ASUPRA UNOR INDICI FENOTIPICI LA PLANTELE DE TOMATE - Mărîi, Liliana; Andronic, Larisa; Sahanovschih, Marionela; Ionaşcu-Urechii, Angela (CEP USM, 2024)
The study aims to investigate the tomato plants response to heat stress applied at the germination and seedling stages, evaluating certain phenotypic parameters in order to highlight possible particularities associated with adaptability to unfavorable environmental conditions. The research included three tomato genotypes with determined stress reactions that were designed into four variants: optimal-optimal, optimal-stress, stress-optimal, and stress-stress. The application of high temperatures at the germination stage significantly affects the subsequent development of tomato plants, resulting in a decrease in the average values of morphological traits compared to optimal conditions variants. The effects of heat stress vary depending on the genotype and the analyzed trait, with certain variants exhibiting specific vulnerabilities. Variance analysis shows that the temperature conditions and the stress application scheme significantly contribute to the variability of morphological traits, with stress at the germination stage having a dominant impact on architectural traits of plants, while genotype becomes the major influencing factor at the seedling stage. The results emphasize the importance of plant adaptability to thermal stress at different developmental stages.
THE EFFECTS OF HIGH TEMPERATURE AT DIFFERENT ONTOGENETIC STAGES ON SOME PHENOTYPIC INDICES IN TOMATO PLANTS
Keywords: phenotypic character; germs; plant; thermal stress; tomato; caracter fenotipic; germene; plantă; stres termic; tomate